Network Pharmacology Analysis of Huangqi Jianzhong Tang Targets in Gastric Cancer - Li, Long; Lu, Yizhuo; Liu, Yanling; Wang, Dan; Duan, Linshan; Cheng, Shuyu; Liu, Guoyan (Frontiers in Pharmacology, 2022)
Background: The Chinese medicine, Huangqi Jianzhong Tang (HJT), is widely used to treat gastric cancer (GC). In this study, network pharmacological methods were used to analyze the potential therapeutic targets and pharmacological mechanisms of HJT in GC. Methods: Bioactive components and targets of HJT and GC-related targets were identified using public databases. The protein-protein interaction network of potential targets of HJT in GC was constructed using the Cytoscape plug-in (v3.8.0), CytoHubba. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed, in addition to molecular docking and animal experiments to verify the results of network pharmacology analysis. Results: A total of 538 GC-related targets were identified. The bioactive components of HJT were selected for drug-likeness evaluation and binomial statistical model screening, which revealed 63 bioactive components and 72 targets. Based on GO enrichment analysis, all targets in the protein-protein interaction network were mainly involved in the response to oxidative stress and neuronal death. Further, KEGG enrichment analysis suggested that the treatment of GC with HJT mainly involved the Wnt signaling pathway, PI3K-Akt signaling pathway, TGF-β signaling pathway, and MAPK signaling pathway, thereby providing insights into the mechanism of the effects of HJT on GC. Conclusion: This study revealed the potential bioactive components and molecular mechanisms of HJT, which may be useful for the treatment of GC, and provided insights into the development of new drugs for GC.